2018
DOI: 10.1155/2018/9368918
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Knowledge Assessment: Newly Graduated versus Senior Dental Clinicians

Abstract: The present study assessed the level of dentists' knowledge regarding oral cancer in the city of São Paulo, Brazil. A questionnaire was used to compare the level of knowledge among newly graduated and senior clinicians. A total of 20,154 e-mails were correctly delivered to the dentists registered in the database of the Regional Dentistry Council of São Paulo, and 477 (2.36%) responses were received. This sample consisted of 84 newly graduated clinicians and 105 senior clinicians. For the statistical analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
38
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 39 publications
3
38
1
4
Order By: Relevance
“…When asking about the OC common stage in Egypt, 76.25% of our participants identified the stage whereas only 24% of respondents awarded the relation between the size of the swelling and OC stage. These results were close to findings of Al‐Maweri et al in Saudi Arabia, but 74.6% of dentists in a Brazilian in the study identified the relation of size and OC stage (Al‐Maweri et al, ; Pavao Spaulonci et al, ). The awareness of our dentist about OC risk factors was high as all of them recorded smoking tobacco and alcohol consumption and over 80% mentioned that family history, HPV, poorly fitted dentures, sun exposure, and consumption of hot beverages and foods are risk factors.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…When asking about the OC common stage in Egypt, 76.25% of our participants identified the stage whereas only 24% of respondents awarded the relation between the size of the swelling and OC stage. These results were close to findings of Al‐Maweri et al in Saudi Arabia, but 74.6% of dentists in a Brazilian in the study identified the relation of size and OC stage (Al‐Maweri et al, ; Pavao Spaulonci et al, ). The awareness of our dentist about OC risk factors was high as all of them recorded smoking tobacco and alcohol consumption and over 80% mentioned that family history, HPV, poorly fitted dentures, sun exposure, and consumption of hot beverages and foods are risk factors.…”
Section: Discussionsupporting
confidence: 90%
“…Years of experience Motallebnejad & Hedayati, 2006). There was not a big difference between positive answers to the common age of OC, the initial aspect of OC, leukoplakia as a common condition associated with OC, and the characteristics of metastasized lymph nodes among our participants, and surveys were done in Italy, Brazil, and Iran (Colella et al, 2008;Pavao Spaulonci et al, 2018;Razavi et al, 2013). There was a wide variation among studies regarding the common site of the OC.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations